2015
DOI: 10.1007/s00264-015-2937-x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal vascular stem cell treatment decreases muscle fibrosis following chronic rotator cuff tear

Abstract: PURPOSE Rotator cuff injuries are associated with atrophy and fat infiltration into the muscle, commonly referred to as "fatty degeneration." As the poor function of chronically torn muscles may limit recovery after surgical repair, there is considerable interest in finding therapies to enhance muscle regeneration. Stromal vascular stem cells (SVFCs) can improve muscle regeneration in other chronic injury states, and our objective was to evaluate the ability of SVFCs to reduce fibrosis and fat accumulation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
(42 reference statements)
1
26
0
1
Order By: Relevance
“…This is consistent with previous investigations suggesting that ASC secretome is capable of reducing lipid content in rotator cuff injuries . This finding however, is not consistent amongst the literature where injections of human vascular and adipose‐derived stem cells isolated from human stromal vascular fraction did not display significant changes in lipid reduction …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is consistent with previous investigations suggesting that ASC secretome is capable of reducing lipid content in rotator cuff injuries . This finding however, is not consistent amongst the literature where injections of human vascular and adipose‐derived stem cells isolated from human stromal vascular fraction did not display significant changes in lipid reduction …”
Section: Discussionsupporting
confidence: 84%
“…33 This finding however, is not consistent amongst the literature where injections of human vascular and adipose-derived stem cells isolated from human stromal vascular fraction did not display significant changes in lipid reduction. 34 Upon denervation, the local cellular environment of skeletal muscle becomes altered, where presence of inflammatory cells amongst the muscle fibers increases. 35 Dual-IF staining was performed to assess macrophage presence as macrophages are essential to muscle turnover in normal and degenerative states.…”
Section: Discussionmentioning
confidence: 99%
“…In separate studies, Oh et al . and Gumucio et al . have reported the potential efficacy of adipose‐derived MSCs in repairing supraspinatus and subscapularis muscle tears and attenuating fibrosis in models of rotator cuff injury.…”
Section: Advances In Treatment Of Local Muscle Injuriesmentioning
confidence: 99%
“…[127][128][129] BM-MSCs also improved muscle contractility by promoting new myofiber formation in a sphincterotomy injury model in rats, indicating their potential utility in treating incontinence. 130,131 In separate studies, Oh et al 132 and Gumucio et al 133 have reported the potential efficacy of adipose-derived MSCs in repairing supraspinatus and subscapularis muscle tears and attenuating fibrosis in models of rotator cuff injury. In injury models of volumetric muscle loss, improved muscle function (contractility) and structure (myofiber formation, reduction of scar tissue, increased blood vessel density) have been observed using MSCs from adipose tissue, 134,135 bone marrow, 136 cranial neural crest, 137 and tonsil.…”
Section: Cellular Therapiesmentioning
confidence: 99%
“…Finally, immediate repair after laceration also does not mimic the clinical scenario in which tendon tears are usually left untreated for weeks or months prior to repair. To model delayed repair, a few groups recently carried out supraspinatus tendon detachment followed by surgical repair 3–16 weeks later . Prolonged unloading resulted in tendon retraction, muscle atrophy, fatty infiltration, and fibrotic scarring.…”
Section: Rotator Cuff Injury Modelsmentioning
confidence: 99%